Influence of removal of a non-native tree species Mimosa caesalpiniifolia Benth. on the regenerating plant communities in a tropical semideciduous forest under restoration in Brazil - Podadera, Diego Sotto [UNESP]; Engel, Vera Lex [UNESP]; Parrotta, John A.; Machado, Deivid Lopes [UNESP]; Sato, Luciane Missae [UNESP]; Durigan, Giselda (Springer, 2015)
Exotic species are used to trigger facilitation in restoration plantings, but this positive effect may not be permanent and these species may have negative effects later on. Since such species can provide a marketable product (firewood), their harvest may represent an advantageous strategy to achieve both ecological and economic benefits. In this study, we looked at the effect of removal of a non-native tree species (Mimosa caesalpiniifolia) on the understory of a semideciduous forest undergoing restoration. We assessed two 14-year-old plantation systems (modified taungya agroforestry system; and mixed plantation using commercial timber and firewood tree species) established at two sites with contrasting soil properties in São Paulo state, Brazil. The experimental design included randomized blocks with split plots. The natural regeneration of woody species (height ≥0.2 m) was compared between managed (all M. caesalpiniifolia trees removed) and unmanaged plots during the first year after the intervention. The removal of M. caesalpiniifolia increased species diversity but decreased stand basal area. Nevertheless, the basal area loss was recovered after 1 year. The management treatment affected tree species regeneration differently between species groups. The results of this study suggest that removal of M. caesalpiniifolia benefited the understory and possibly accelerated the succession process. Further monitoring studies are needed to evaluate the longer term effects on stand structure and composition. The lack of negative effects of tree removal on the natural regeneration indicates that such interventions can be recommended, especially considering the expectations of economic revenues from tree harvesting in restoration plantings.
Keywords: Adaptive management; Atlantic forest; Ecological restoration; Natural regeneration; Seasonal semideciduous forest; Thinning